Asasi Newsletter: Issue No. 1 (October 2014) - Centre of, Foundation Studies (Centre of Foundation Studies, 2014)
Congratulations to the Research Bulletin Committee for successfully publishing our first edition of Asasi Newsletter. In this newsletter, all the research papers presented in seminars and conferences by the Centre of Foundation Studies' (CFS) lecturers are being compiled for knowledge sharing. I am very pleased to see a considerable number of research papers being presented both locally and abroad. This noble effort will certainly put UiTM on the world map. Although CFS is very much a teaching and learning centre at the preparatory level, each and every lecturer is expected to do research and present his/her findings as technical papers in conferences or publish them in journals. CFS is always supportive of lecturers who carry out research activities as this will enhance their career progression. Lecturers are also encouraged to link themselves with research groups from other faculties so as to overcome our limited resources. I wish to see more research output when we move to our new campus in Dengkil next year. Best of Luck!!